PENGARUH PENERAPAN PEMBELAJARAN MENDALAM (DEEP LEARNING) TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SD MUHAMMADIYAH KARANGTURI - Arviana Ayu Kurnia Dewi; Ani Rusilowati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of deep learning on the IPAS learning outcomes of fifth-grade elementary school students. A quasi-experimental method with a nonequivalent control group design was used. The sample consisted of 40 students divided into experimental and control classes. Data were collected through a 15-item multiple-choice test administered as a pretest and posttest. Results showed a significant difference between the posttest scores of the experimental and control groups. The experimental class achieved an average posttest score of 94.60, higher than the control class average of 86.05. The t-test revealed a significance value of 0,001 (p < 0.05), with an effect size (Cohen's d) of 1.15, indicating a high level of effectiveness. Thus, deep learning is proven effective in enhancing students' IPAS learning outcomes.